(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
The main approach of the Nanocochleates is to target the cancer cells for the effective treatment against leukemia. Nanocochleate is more stable than any other drug carriers such as Liposomes, Niosomes, Nanoparticles and Nanoliposomes. Nanocochleate drug delivery is most effective in case of both hydrophilic and hydrophobic drugs. Cytarabine is used for the leukemic treatment since long time and its pharmacological effect is well established for the nanocochleate preparation, as it is suitable for the formulation: by increasing the half-life, to avoid getting converted to inactive metabolite by intestinal enzymes, increases the permeability, reduces the dose etc. The storage and release of the conventional dosage form was affected by environmental factors as it can be overcome by the nanocochleates. Nanocochleates are prepared by using the various cross-linking agent like, calcium chloride, zinc chloride and chitosan. The Nanocochleates is optimized by the Response surface methodology using a Box and Behnken’s design, as it allows the determination of various factors on nanocochleates properties with a minimum number of experiments. The drug loaded Nanocochleates was prepared with high entrapment efficiency and prolonged drug release. From the results it can be concluded that the novel Nanocochleates drug delivery system has a promising carrier for treatment of leukemia.